35. THE PREVALENCE OF MALNUTRITION AND RELATED FACTORS AMONG PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AT PHAM NGOC THACH HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the prevalence of malnutrition and related factors patients with chronic obstructive pulmonary disease at Pham Ngoc Thach Hospital in 2023. Methods: A cross-sectional study was conducted on 84 patients with chronic obstructive pulmonary disease within 48 hours after hospitalization at Pham Ngoc Thach Hospital, from October 2022 to June 2023. The collected information includes nutritional status (SGA, BMI, muscle mass), characteristics of sociology and pathology in addition to laboratory findings. Results: The malnutrition rate in chronic obstructive pulmonary disease patients was 44.1% (according to SGA method); this rate was 23.9% with BMI index. There was the connection between malnutrition (according to SGA) in patients with chronic obstructive pulmonary disease and the number of lymphocytes (p
Keywords: Malnutrition, COPD, SGA, lymphocytes, muscle mass.